Study on thermodynamics of glycerol hydrogenolysis to high value-added diols - Liu Liping; Cui Yu; Chen Shuo; Fang Shuqi (E3S Web of Conferences, 2020)
The thermodynamic process on hydrogenolysis of glycerol to high value-added diols was studied. The thermodynamic parameters of the main reaction equations were calculated, and the effects of temperature, pressure and molar ratio of hydrogen to glycerol on the products of the reaction equilibrium system were analysed. The deep hydrogenolysis system of glycerol and the degradation of its diols are also discussed. The results show that temperature has a great influence on the selectivity of the products. 1,2-propanediol is more easily formed. The optimum conditions for hydrogenolysis of glycerol to 1,2-propanediol are 400-500 K and the molar ratio of hydrogen to glycerol of 1.0-1.5. The calculated results are compared with the related experimental results.